2013
DOI: 10.1350/ijps.2013.15.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Errors in the Identification of Question Types in Investigative Interviews of Children

Abstract: This study examined the incidence and nature of the errors made by trainee coders during their coding of question types in interviews in which children disclosed abuse. Three groups of trainees (online, postgraduate and police) studied the coding manual before practising their question coding. After this practice, participants were given two-page field transcripts to code in which children disclosed abuse. Their coding was assessed for accuracy; any errors were analysed thematically. The overall error rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Recent studies have begun to highlight the benefits of having interviewer trainees code and objectively evaluate their own interviews (Cederborg, Alm, Lima da Silva Nises, & Lamb, ; Stolzenberg & Lyon, ). Guided self‐evaluation not only reduces the professional dependence of investigators on mentors and supervisors, but fosters the skilled identification of successful interventions (Powell, Benson, Sharman, & Guadagno, ; Yii, Powell, & Guadagno, ) as well as the ability to critically evaluate adherence to best practice guidelines (Cederborg, Alm, & Lima da Silva Nises, & Lamb, ; Myklebust & Bjørklund, ; Orbach et al, ; Price & Roberts, ) and is greatly appreciated by trainees (Powell & Wright, ). Such training often involves teaching interviewers to code their own interviews systematically using scientific procedures and formal coding schemes (Cederborg et al, ; Warren et al, ; Yi et al, ).…”
Section: Child Forensic Interviewer Training Studiesmentioning
confidence: 99%
“…Recent studies have begun to highlight the benefits of having interviewer trainees code and objectively evaluate their own interviews (Cederborg, Alm, Lima da Silva Nises, & Lamb, ; Stolzenberg & Lyon, ). Guided self‐evaluation not only reduces the professional dependence of investigators on mentors and supervisors, but fosters the skilled identification of successful interventions (Powell, Benson, Sharman, & Guadagno, ; Yii, Powell, & Guadagno, ) as well as the ability to critically evaluate adherence to best practice guidelines (Cederborg, Alm, & Lima da Silva Nises, & Lamb, ; Myklebust & Bjørklund, ; Orbach et al, ; Price & Roberts, ) and is greatly appreciated by trainees (Powell & Wright, ). Such training often involves teaching interviewers to code their own interviews systematically using scientific procedures and formal coding schemes (Cederborg et al, ; Warren et al, ; Yi et al, ).…”
Section: Child Forensic Interviewer Training Studiesmentioning
confidence: 99%
“…It may be correct to assert that questions that begin with “tell me” are likely to be open-ended, but only if wh- prompts are considered open-ended. However, many researchers, such as Powell and her colleagues, reserve the term open-ended for questions that would qualify as invitations (Powell et al, 2013; Powell & Snow, 2007). This can add to practitioners’ confusion, because although they are universally advised to maximize their use of open-ended questions, they may be unsure of how those questions are best defined.…”
Section: True and Faux Invitationsmentioning
confidence: 99%
“…Yi and Lamb (2018), testing Korean police officers trained to use the NICHD protocol, found that trainees sometimes misclassified wh- prompts as invitations (20%) and invitations as wh- prompts (10%). Powell and colleagues (2013), studying research assistants, online forensic interviewing trainees, and police trainees ability to classify questions as invitations, found that the most common error was to overlook “what happened” questions as invitations (13% of errors; what they called “open-ended”), and the third most common error was to overcall “tell me” questions as invitations (5% of errors).…”
Section: True and Faux Invitationsmentioning
confidence: 99%
“…It may be correct to assert that questions that begin with "tell me" are likely to be open-ended, but only if wh-prompts are considered open-ended. However, many researchers, such as Powell and her colleagues, reserve the term open-ended for questions that would qualify as invitations (Powell, Benson, Sharman, Guadagno, & Steinberg, 2013;Powell & Snow, 2007). This can add to practitioners' confusion, because although they are universally advised to maximize their use of open-ended questions, they may be unsure of how those questions are best defined.…”
Section: True and Faux Invitationsmentioning
confidence: 99%